Gestão e análise de dados para desenvolvimento de diretrizes para planos diretores hospitalares - Marcolla, Marcelo Jose (2020)
This research was motivated by the professional experience of the author of this dissertation, in the area of hospital planning, experienced in an EAS, which, like other hospital buildings, has historically been impacted by new programmatic demands, society dynamics, and especially with new technologies in medicine, situations that have been causing the obsolescence of existing hospital structures, generating spatial, infrastructure, and consequently legal difficulties. Identifying that the research aims to enable the design guidelines in the built hospital environment to be made feasible, in order to promote the quality of the project in the light of performance, it was developed with the support of the APO methodology, which aims to assess a set user needs in the use of the built environment. The object of study was a regional hospital located in the metropolitan region of Curitiba, which was analyzed in its physical-spatial aspects at different scales, as well as in the application of questionnaires with five groups of users, identified by sampling. The results of the questionnaires identified different perceptions of users about the experienced space, as well as a sectorial mapping that related to macro, meso and micro analyzes, gave support to diagnose and promote theoretical and spatial prognoses, and with this, identify guidelines at different scales, creating thus a mapping of the actions for a PDH, not only for the HMSJP, object of this case study, but as a reference of systematization for other EAS´s.